OPTICAL NANOANTENNAS FOR PHOTOCATALYSIS AND SINGLE-MOLECULE SPECTROSCOPIC APPLICATIONS - CHARANLEEN KAUR (My University, 2025)
The present thesis delves into exploring the diverse uses of optical nanoantennas, including single molecule sensing, fluorescence enhancement, photocatalysis, electrocatalysis, and lot more. Plasmonic nanostructures form the building blocks of optical nanoantennas. They are excellent choices because of their distinctive plasmonic properties, specifically referred to as localized surface plasmon resonance (LSPR). The tuning of LSPR for plasmonic nanostructures is achievable by modifying the size, morphology, composition, interparticle spacing, and dielectric of the medium and metal itself. The localized surface plasmons decay radiatively causing electromagnetic field enhancement and non-radiatively by hot electrons and holes, and plasmonic heat. The combination of electron-hole pairs, strong electric fields, and heat generation during LSP excitation and decay processes enables the various applications mentioned earlier. Anisotropic plasmonic nanostructures significantly boost the signals of Raman and fluorescence. Gold, renowned for its stability, is a superior plasmonic material commonly employed in nanoplasmonics due to its exceptional properties. On the other hand, when different varieties of plasmonic metal nanostructures are merged such as core-shell nanostructures, they possess the ability to generate exceptional plasmonic functionalities, rendering them appealing for various applications. Building upon the context outlined previously, the third chapter of the thesis involves a structured method for designing a custom arrangement of Gold nanobipyramids (Au NBPs) monomer and dimer nanoantenna engineered precisely based on DNA origami technique. Utilizing these precisely arranged nanostructures, Surface-Enhanced Raman Spectroscopy based detection of Thioflavin T (ThT), a well-established marker for the detection of amyloid fibrils formation was carried out where G Quadruplexes govern the site-specific attachment of ThT in the plasmonic hotspot. Au NBPs were selected as the anisotropic plasmonic linear nanostructures to achieve the objectives of the thesis. These sharp-tipped, monodisperse nanostructures were synthesized using a bottom-up, solution-based approach. The synthesized Au NBPs were thoroughly characterized using various analytical techniques, including UV-Vis spectroscopy, Transmission Electron Microscopy (TEM), X-Ray Diffraction (XRD), X-Ray Photoelectron Spectroscopy (XPS), and Energy-Dispersive X-Ray Spectroscopy (EDX). To attain single-molecule sensitivity, dimer structures were engineered to exhibit significant electromagnetic field amplification at the junction between the two Au NBPs, known as the hot spot region. This hot spot is the ideal location to position a single molecule for spectroscopic investigations. DNA origami is employed as a modulating template to assemble the Au NBP dimers in the desired orientation. DNA origami is a solution-based self-assembly method that involves a single long DNA strand and numerous short DNA sequences under specific buffer conditions, typically utilizing a thermocycler for controlled assembly. This study paves the way to boost the design of next-generation diagnostic tools for specific, precise detection of various target disease biomarkers using molecular probes. Further, the fourth chapter of the thesis includes the synthesis of core-shell nanostructures, which offer enhanced potential for spectroscopic applications by integrating the advantages of two distinct materials within a single, hybrid structure. These nanostructures were used as a photocatalyst in this chapter. The unique influence of shape, material composition, and temperature on the photocatalytic process was studied. The efficiency of Au NBPs with distinctive sharp ends and core shell nanobipyramids (Au@Ag NBPs) was monitored for the conversion of 4 mercaptophenyl boronic acid (4-MPBA) to benzenethiol (BT) using SERS. The reaction efficiency is notably superior in Au NBPs (57%), attributed to their sharp tips, leading to enhanced yields in comparison to Au@Ag NBPs (45%). Additionally, Au NBPs exhibit faster reaction times than previously documented. Leveraging the stronger plasmonic effect of silver over gold, Au@Ag NBPs demonstrated more intense peaks and enabled reactions at lower reactant concentrations than Au NBPs. The next chapter includes the investigations on single molecule fluorescence enhancement of Atto 647N dye precisely located using DNA origami. The DNA origami technique has enabled the creation of intricate nanoscale geometries that strategically position a single fluorophore near the overlapping plasmonic fields of nanostructures, setting a new standard for effectively harnessing coupled electromagnetic radiation. The metallic arrangements utilized mirrored those discussed in the third chapter. The strong coupling between single quantum emitters and plasmonic nanostructures has enabled the development of plasmonic devices for diagnostic platforms. This coupling leads to significant modifications in the emission properties of fluorescent emitters, such as enhanced excitation rates and quantum yields. By precisely controlling the spatial distribution of the emitters relative to the plasmonic near-field, the emission can be further optimized. These advancements have paved the way for the realization of highly sensitive plasmonic-based diagnostic devices that can operate at the single-molecule level. Further, the sixth chapter of the thesis focuses extensively on the predominant role of Au NBP dimer formation in initiating the electrocatalytic activity of the water splitting reaction using a primarily DNA origami template. The sluggish kinetics of oxygen evolution reaction (OER) make it a bottleneck in water splitting, leading to growing research interest in improving its efficiency and thereby increasing H2 production. Through the strategic integration of DNA origami technology and Au NBP nanostructures, this study aimed to orchestrate precise modulation of the electrocatalyst's architecture to achieve unprecedented levels of activity in the OER. The dimer configuration facilitated controlled assembly and spatial arrangement of Au NBPs, optimizing the exposure of catalytically active sites and promoting efficient charge transfer pathways leading to an overpotential of 146 mV for Au NBP dimer catalyst to achieve a current density of 10 mA cm-2. This thesis encapsulates the remarkable efficacy and versatility of anisotropic plasmonic nanostructures, including gold nanobipyramids and gold core-silver shell nanobipyramids.
Keywords: NANOANTENNAS; nanobipyramids